Improved Design of Lifting Slide Rail System of Stone Processing Machine. Issue 1 (1st January 2022) - Zhang, Jing; Yang, Kaihuai; Lin, Shengfeng; Lin, Yanqing; Chen, Taili; Cheng, Yan; Gao, Hua; Hu, Xingye
Abstract: In this research, improved design for the lifting slide rail system on stone processing machine has innovated in a few aspects, including the innovative design of the lifting rail, fixture to fix and connect with the hydraulic tappet, and the sliding block equipped with limit device etc. The improved design has been successfully applied to the stone processing machine to crush and process block and stone flake processing waste of different shapes, it turned out that the needle flake particle content and crushing index of the processed stone are in line with the national standard requirements, i.e. crushing index of 7.2%, reaching the technical requirements of Class I crushed stone. In another words, the improved design has significantly improved the processing efficiency and safety and reduced costs effectively; meanwhile, its handy operation and utilization has made it ready to promote in a wider range.